Estudio de empleabilidad de graduados de la carrera Administración Pública de la Escuela Superior Politécnica Agropecuaria de Manabí MFL período 2017-2019 - Bazurto Muñoz, Jenniffer Juliana (2022)
The objective of this research was to determine the level of employability of the graduates of the Public Administration career at Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López" in the periods 2017-2019, for the improvement of their professional profiles. Within the methodology used, the technique of the survey applied to both the graduates of the career who provided information on the current employment situation, and the representatives of public sector organizations, in order to know the most important elements or aspects when selecting university graduates, on the other hand, within the research methods that were carried out, there are the inductive, the narrative, the deductive and the analytical, which allow to understand the problem and its characteristics. In the results, 58% of the graduates have a formal job in different areas, it is important to note that within this figure, 38% have their own business that generates income due to the difficulties that arise when obtaining a job, since work experience, postgraduate studies, complementary training, are highly valued by organizations when hiring human capital, unlike other elements that are not as essential for the purpose as knowledge of languages or technology. Finally, an improvement plan is proposed to contribute to the solution of the problem.